Legal situation of the Jewish minority in the territories controlled by the League of Nations in the 1930s: Upper Silesia – Territory of Saarland – Danzig (Zaranie Śląskie, 2023)
The following article provides an overview of the legal situation of the Jewish population in Upper Silesia,Saarland and the Free City of Danzig. All three areas were under the influence of the League of Nationsin the interwar period. Firstly, it outlines how the protection of minorities, as enshrined in the Treatyof Versailles, among others, affected the respective territories in the interwar period in the 1930s. Secondly,it is shown how the Jews attempted to resist anti-Jewish legal measures within this legal framework of minority protection. It is shown that the legal instrument of petitioning the League of Nations was frequentlyused, but had little impact on the progressive disenfranchisement of the Jews in the 1930s.
Keywords: Jewish minority; legal situation; Treaty of Versailles; League of Nations; persecution